An Optimized Approach to Perform Bone Histomorphometry - Malhan, Deeksha; Muelke, Matthias; Rosch, Sebastian; Schaefer, Annemarie B.; Merboth, Felix; Weisweiler, David; Heiss, Christian; Arganda-Carreras, Ignacio; El Khassawna, Thaqif (Frontiers in Endocrinology, 2018)
Bone histomorphometry allows quantitative evaluation of bone micro-architecture, bone formation, and bone remodeling by providing an insight into cellular changes. Histomorphometry plays an important role in monitoring changes in bone properties due to systemic skeletal disease like osteoporosis and osteomalacia. Besides, quantitative evaluation plays an important role in fracture healing studies to investigate the effect of biomaterial or drug treatment. However until today, to our knowledge, bone histomorphometry remain time-consuming and expensive process. This instigated us to establish an open-source freely available semi-automated solution to measure parameters like trabecular area, osteoid area, trabecular thickness, and osteoclast activity. Here in this study, the authors present the adaptation of Trainable Weka Segmentation plugin of ImageJ to allow fast evaluation of bone parameters (trabecular area, osteoid area) to diagnose bone related diseases. Additionally, ImageJ toolbox and plugins (BoneJ) were adapted to measure osteoclast activity, trabecular thickness, and trabecular separation. The generated scripts are based on ImageJ, thereby providing simple user-interface and easy accessibility for biologists and clinicians. The scripts developed for bone histomorphometry can be optimized globally for other histological samples. The established scripts will benefit the scientific community in histological evaluation.